Genomic and functional characterization of the lect2 gene from Siniperca chuatsi. Issue 107 (December 2020) - Shen, Yawei; Cao, Ming; Tang, Shoujie; Zhao, Yan; Zhao, Jinliang; Chen, Xiaowu; Bi, Yanhui
Abstract: Mandarin fish ( Siniperca chuatsi ) is an important economic fish in China. Viral and bacterial diseases seriously affect the artificial culture of S. chuatsi . As a carnivorous fish, artificial feed domestication is also an important means to improve the scale of S. chuatsi culture. Therefore, the study of immunology and digestive physiology is very important to the industrial development of S. chuatsi . In this work, we analyzed the expression and function of the S. chuatsi leukocyte cell-derived chemotaxin 2 ( Sc-lect2 ) gene on a basis of next generation, single-molecule long-read sequencing. Sc-lect2 was mainly expressed in the liver but barely expressed in the gill, skin, muscle, kidney, head kidney, brain, stomach, and intestine. When the fish were infected with infectious spleen and kidney necrosis virus and challenged with lipopolysaccharide and polyinosinic–polycytidylic acid, Sc-lect2 expression significantly increased by about 40, 17, and 7-fold, respectively, compared with unstimulated samples. We also found that Sc-lect2 increases by approximately 8-fold after the fish are fed an artificial diet. These results show that mandarin fish liver can not only digest food but also express specific immune genes. Changes in the diet can cause the differential expression of Sc-lect2 genes. Four Sc-lect2 interaction genes were differentially expressed in the skin or blood. Interestingly, miR-145–3p could inhibit Sc-lect2 gene expression by targeting its coding sequence region. One CpG island in the promoter region showed a high level of methylation, suggesting that high methylation does not affect Sc-lect2 gene expression in the liver. Highlights: Lect2 Gene is specifically expressed in the liver. Lect2 can be up-regulated after ISKNV infection, LPS or I:C induction. Artificial feed can also cause the differential expression of lect2 genes. miR-145–3p could inhibit lect2 gene expression by targeting its coding sequence region.